Sistem Pengolah Data Akreditasi Program Studi Universitas Negeri Semarang - Fauzi, Mas'ul; Widodo, Djoko Adi (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
According to the Higher Education Act Section Nine of Education and Learning Process Studies Paragraph 1 of Article 33, paragraph 3, which reads